GEOTECHNICAL PROCESSES AND SOIL-WATER MOVEMENT WITH TRANSPORT OF POLLUTANTS IN THE ESTONIAN OIL SHALE MINING AREA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
One of the most important industries of Northeast Estonia is oil shale mining. Ground movements caused by mining reach the ground surface easily due to shallow location of workings. A new, artificial topography is formed on undermined areas, where the ground surface depressions are alternating with rising grounds. When the Quaternary cover contains loamy sediments, the surface water will accumulate in the depressions. The response of usable lands on undermined areas depends on the degree of changes in the relief and water regime. The accumulation of solid residues by oil shale mines and processing plants has resulted in numerous ash hills, which are polluting the environment. The streams are polluted by phenols, oil products and sulphates. The main source of water supply is groundwater in the oil shale basin. The hydrostratigraphic section is represented by three aquifers. Two (Quaternary and Ordovician) of these aquifers are affected by the human activity. Intensive water consumption has caused a fall in the water level in these aquifers. Due to oil shale production the concentration of Ca2+, Mg2+, SO4 2- and Cl- contained in the groundwater from the Ordovician deposits is noticeably higher than in the water with a natural background level. The natural water chemical regime is restored at the cessation of mining.